Inovasi E-modul Berdiferensiasi Berbasis PjBL Materi Bentang Alam Untuk Meningkatkan Kolaborasi Siswa Kelas IV SD di Kabupaten Blitar: Inovasi E-modul - Haryanti, Alfi; Alfi, Cindya; Oktaviani, Ragil Tri (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
This study aims to create a differentiated E-module based on Project Based Learning (PjBL) on landscape material to improve the collaboration of grade IV elementary school students in Blitar Regency. Research and development are carried out using the ADDIE paradigm which consists of the stages of analysis, design, development, implementation, and evaluation. The ADDIE paradigm, which consists of the phases of analysis, design, development, implementation, and evaluation methodology used in this work. Three experts material, media, and language experts performed product validation, and instructors assessed the viability of the product. According to the validation evaluation, the created e-module received a very valid category from the following aspects: language (82%), media (95%), and material (95%). With a 91% success rate, the teachers' feasibility test likewise produced extremely feasible outcomes. The implementation of e-modules with an N-Gain value of 0.72, students demonstrated significant improvement in collaboration. Therefore, this unique PjBL-based e-module helps students work better together and is suitable for use as a learning resource in landscape learning in elementary schools.